Hawley's condensed chemical dictionary - Sax, N. Irving; Richard, I. Leusis (New Delhi, 1990)
The Condensed Chemical Dictionary is a unique publication. It is not a dictionary in the usual sense of a compilation of brief definitions but rather a compendium of technical data and descriptive information covering many thousand chemicals and chemical phenomena organized in such a way as to meet the needs of those who have only minutes to devote to any given substance or topic. Three distinct types of information are presented: descriptions of chemicals raw materials processes and equipment; expanded definitions of chemical entities phenomena and terminology; and description or identification of a wide range of trademarked products used in the chemical industries. Supplementing these are listings of accepted chemical abbreviations used in the literature short biographies of chemists of historic importance and descriptions or notations of the nature and location of many American technical societies and trade associations. In special cases editorial notes have been supplied where it was felt necessary to clarify or amplify a definition or description.
Keywords: PHARMACOPOEIA/FORMULARIES; GENERAL REFERENCE